Interdisciplinary approach to treat dyskeratosis congenita associated with severe aplastic anemia: A case report - Gomes, Mônica Fernandes [UNESP]; De Abreu, Paula Pinheiro [UNESP]; Banzi, Éfani Caroline de Freitas [UNESP]; Nogueira, Terezinha de Oliveira [UNESP] (Wiley, 2006)
This paper reports on a 4-year-old male who had dyskeratosis congenita and who acquired severe aplastic anemia. The patient developed hyperpigmentation of the face, neck and chest region, arms, shoulders and legs. In addition, he had dry skin, deformed fingernails and toenails, sparse hair and eyebrows and hyperkeratosis of the dorsum of the hands and feet. Laboratory and histological analysis revealed severe pancytopenia and dyserythropoiesis of red blood cells, hypocellularity of white blood cells and decreased megakaryocytes with dysplasia. The intraoral examination identified bleeding gums; petechiae of the palate, tongue and cheek mucosa; and an atrophic, smooth and shining dorsal surface of the tongue. There were deep carious lesions in the deciduous mandibular molars and maxillary anterior teeth; as well as mobility of mandibular left canine, which had bone loss. The treatment for oral lesions included diet changes, improved oral hygiene, and extraction of the deciduous teeth destroyed by caries.
Keywords: Aplastic anemia; Congenita; Dyskeratosis; Interdisciplinary team; Oral manifestations; Special care; aplastic anemia; case report; dental care; dental caries; dental surgery; dyskeratosis congenita; hospitalization; human; male; methodology; mouth hygiene; periodontal disease; preschool child; treatment outcome; Anemia, Aplastic; Child, Preschool; Dental Care for Children; Dental Care for Chronically Ill; Dental Caries; Dental Restoration, Permanent; Dyskeratosis Congenita; Humans; Male; Oral Hygiene; Periodontal Diseases; Severity of Illness Index; Treatment Outcome